Female Empowerment on International Women's Day 2023 Ads: Critical Discourse Analysis of Mercedes-Benz “Be One of Many” - Salelatu, Maria Kristina; Isnaini, Santi; Wibawa, IGAK Satrya (Lingua Susastra, 2023)
Female representation in the media had been drastically changed as the women empowerment was put into the spotlight in international society, including the Western countries. The feminism movement had stimulated various creative content, including in the emotional advertisements where brands were trying to build a closer relation with their customers instead of the usual hard-selling ads. Femvertising was one of the products of women empowerment in the creative industry; in short, it referred to advertisements made with messages to support girls and women. This study was aimed to find out the discourse strategies of current femveritising in conveying female empowerment message. this article conducted a qualitative study of video ads by Mercedes-Benz titled “Be One of Many” and the findings were presented in descriptive format. The data analysis was conducted by using Sara Mills’ model of Critical Discourse Analysis. The findings showed that the 2023’s International Women’s Day femvertising put women as their main subjects and also conveyed a specific “women support women”. In conclusion, current femvertising’s aim went beyond empowering oneself to be better than others or to be either the first or only woman in a profession or field, instead women should empower each other so that more women would achieve their dream and success even in the fields that are still dominated by men.